2011
DOI: 10.1002/chem.201003581
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of Helicobacter pylori Lipopolysaccharide Partial Structures and their Selective Proinflammatory Responses

Abstract: Helicobacter pylori is a common cause of gastroduodenal inflammatory diseases such as chronic gastritis and peptic ulcers and also an important factor in gastric carcinogenesis. Recent reports have demonstrated that bacterial inflammatory processes, such as stimulation with H. pylori lipopolysaccharide (LPS), initiate atherosclerosis. To establish the structures responsible for the inflammatory response of H. pylori LPS, we synthesized various kinds of lipid A structures (i.e., triacylated lipid A and Kdo-lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 69 publications
3
57
0
Order By: Relevance
“…In another suggested mechanism of immune evasion, H. pylori was shown to inhibit macrophage release of nitric oxide in response to H. pylori LPS in a mouse model of infection (2). H. pylori LPS was also shown to suppress TLR-4 signaling, but enhance IL-12 and IL-18 production (3), which was suggested to be linked to the chronic inflammation commonly seen during infection. In further support for the role of H. pylori LPS signaling through TLR-2 instead of TLR-4, one group demonstrated that upon TLR-2 activation by LPS derived from H. pylori inhibited the TRIB3 protein, which controls TLR-2-mediated NF-κB signaling, thus leading to increased NF-κB signaling (4).…”
Section: The Innate Response To H Pylorimentioning
confidence: 99%
See 1 more Smart Citation
“…In another suggested mechanism of immune evasion, H. pylori was shown to inhibit macrophage release of nitric oxide in response to H. pylori LPS in a mouse model of infection (2). H. pylori LPS was also shown to suppress TLR-4 signaling, but enhance IL-12 and IL-18 production (3), which was suggested to be linked to the chronic inflammation commonly seen during infection. In further support for the role of H. pylori LPS signaling through TLR-2 instead of TLR-4, one group demonstrated that upon TLR-2 activation by LPS derived from H. pylori inhibited the TRIB3 protein, which controls TLR-2-mediated NF-κB signaling, thus leading to increased NF-κB signaling (4).…”
Section: The Innate Response To H Pylorimentioning
confidence: 99%
“…A further role TLR-2 was shown in addition to TLR-5 expression by H. pylori on THP-1 monocytic leukemia cells resulted in a shift from cagPAI-dependent to cagPAI- independent signalling leading to the secretion of IL-8 and TNF-α (5). In NK cells, TLR-2 was shown to be activated by H. pylori lipoprotein HpaA, leading to IFN-γ production in an IL-12 dependent manner (3, 6). In further analysis of TLR-2 activation by H. pylori , urease was shown to activate TLR-2 on B cells, inducing autoantibodies and suggesting a link to autoimmune disorders (7).…”
Section: The Innate Response To H Pylorimentioning
confidence: 99%
“…Our laboratory has shown that among gastric cancer patients, FAF1 mRNA levels are lower in tissues positive for H. pylori than in tissues negative for H. pylori [7]. H. pylori may increase risk of gastric cancer in part by activating NF-κB signaling [10, 11], leading to secretion of pro-inflammatory cytokines such as tumor necrosis factor-α (TNF-α), interleukin-1 (IL-1β), interleukin-6 (IL-6) and interleukin-8 (IL-8). Therefore we wondered whether FAF1 may be affected by NF-κB signaling.…”
Section: Introductionmentioning
confidence: 99%
“…at À78 to À50 8 8CinCH 2 Cl 2 ( Table 1). Gratifyingly,the thioglycosides 1c-e,b earing a5 ,7-O-DTBS group,e xhibited strong stereocontrol during the condensations with 2 and complete aanomeric selectivity was obtained for the products 3ce (entries [3][4][5]. [4e, 11] For the a-anomer, the 3 J C-1/H-3ax value is 1.0 Hz, while,for the banomer,t he 3 J C-1/H-3ax is 5.0-6.0 Hz.…”
mentioning
confidence: 99%